2020
DOI: 10.3177/jnsv.66.41
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Autophagy and Changes in Cellular Metabolism in Glucose Starved C2C12 Myotubes

Abstract: Mouse myoblast C2C12 cells are commonly used as a model system for investigating the metabolic regulation of skeletal muscle. As it is therefore important to understand the metabolic features of C2C12 cells, we examined the effect of glucose starvation on autophagy in C2C12 myotubes. After culture of C2C12 myotubes with high (HG, 25.0 mm) or low (LG, 5.6 mm) glucose concentrations, the concentration of glucose in the LG group had decreased to 0 mm after 24 h of culture and was around 17 mm after 48 h of cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…Glucose starvation for 24 h decreases the phosphorylation levels of p70S6K. This is in line with previous studies suggesting that glucose is essential to maintain the phosphorylation levels of p70S6K [10,11]. In addition, we found that re-addition of glucose augmented the phosphorylation levels of p70S6K in 24-h glucosestarved cells but not in the nonstarved myotubes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Glucose starvation for 24 h decreases the phosphorylation levels of p70S6K. This is in line with previous studies suggesting that glucose is essential to maintain the phosphorylation levels of p70S6K [10,11]. In addition, we found that re-addition of glucose augmented the phosphorylation levels of p70S6K in 24-h glucosestarved cells but not in the nonstarved myotubes.…”
Section: Discussionsupporting
confidence: 92%
“…Glucose deprivation is a known factor for stimulating protein breakdown. The autophagy-lysosome system [9][10][11] and ubiquitin-proteasome system [28,29] are also reported to be accelerated by glucose starvation. Thus, we examined the role of the autophagy-lysosome system and the ubiquitin-proteasome system in our glucose re-addition-induced activation of p70S6K by using pharmacologic inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that glucose starvation of cells induces autophagy in cells ( Nakai et al, 2020 ). Therefore, we tested whether soot treatment can inhibit starvation-induced autophagy.…”
Section: Resultsmentioning
confidence: 99%
“…Fullerene Soot Inhibits Starvation-Induced Autophagy and Induces Proliferation of A549 Cells, Which Is Reversed by Akt-Inhibitor X It is well established that glucose starvation of cells induces autophagy in cells (Nakai et al, 2020). Therefore, we tested whether soot treatment can inhibit starvation-induced autophagy.…”
Section: Fullerene Soot Inhibits Autophagic and Apoptotic Cell Death Of Human Lung Epithelial A549 Cellsmentioning
confidence: 96%